Paper in design and architecture - Jerzy F. Latka (A+BE: Architecture and the Built Environment)
Paper base products such as corrugated cardboard, paper tubes, honeycomb panels and strong papers like Kraft and Washi can be successfully used for the production of interior design, products for everyday use, furniture, indoor partitions, pavilions and bigger architectural structures. Paper and its derivatives are often used for other purposes such as educational (origami) or social and artistic events.